A common framework for MOOC curricular development in climate change education - Findings and adaptations under the BECK project for higher education institutions in Europe and Asia. (April 2022) - Senevirathne, Malith; Amaratunga, Dilanthi; Haigh, Richard; Kumer, Dhimman; Kaklauskas, Arturas
Abstract: The Sendai Framework for Disaster Risk Reduction has identified the climate change education as a key motivation for improving energy efficiency, climate change adaptation and disaster risk reduction by encouraging changes in the attitudes and behaviour and helping adapt to climate change-related trends. Delivering climate change education via Massive Open Online Courses (MOOC) in higher education is considered as an effective method for wider community engagement, scientific networking, and knowledge sharing. The BECK project funded by the ERASMUS+ Programme is aimed to address this approach by introducing new harmonized MOOC modules to the higher education curricular of 4 European, 5 Russian and 5 Asian higher education institutions (HEI). Based on the cross-institutional capacity needs assessment survey, the project adapted a common framework for the MOOC development and implementation across the partner institutions. The aim of this research is to develop a framework to ensure the curricular development is followed by pedagogical principles while adhering to the quality benchmarks in its implementation. This framework establishes common grounds for BECK MOOC while assisting the partner institutions with necessary capacity building for teaching and learning measures. The BECK project continues to disseminate the MOOC modules via the BECK virtual interuniversity and support the effective implementation of the developed framework. Highlights: The BECK project capacity building framework guides the development of MOOC modules. The quality of the MOOC curricular is assured by adhering to Pedagogical standards. The European best practices are embedded into the MOOC teaching and learning methods. The Interuniversity Educational Centre is developed to disseminate the MOOC modules. The scientific networking for Asian partner institutions is strengthened in overall.